Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5606/ehc.2020.75113
|View full text |Cite
|
Sign up to set email alerts
|

A new proximal femoral nail antirotation design: Is it effective in preventing varus collapse and cut-out?

Abstract: Objectives This study aims to compare the mechanical features of the existing proximal femoral nail antirotation (PFNA) system and the new PFNA system that we designed using three-dimensional (3D) finite element analysis. Materials and methods This experimental study was conducted between 2019 and 2020. We constructed two femur models with Arbeitsgemeinschaft für Osteosynthesefragen (AO) type A1 fractures using 3D computed tomography scans. The new and standard PFNA des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…PFNA is a modification of proximal femoral intramedullary nail and has the following advantages when applied to manage femoral intertrochanteric fractures: (a) the original two lag screws changed to one spiral blade, and the percussion method is adopted during the surgery. is not only reduces intraoperative bone loss but also compresses the cancellous bone in the femoral head and increases the anchoring force [16][17][18]. (b) e spiral blade can be locked by itself with strong holding force, which can play the role of antirotation [19].…”
Section: Discussionmentioning
confidence: 99%
“…PFNA is a modification of proximal femoral intramedullary nail and has the following advantages when applied to manage femoral intertrochanteric fractures: (a) the original two lag screws changed to one spiral blade, and the percussion method is adopted during the surgery. is not only reduces intraoperative bone loss but also compresses the cancellous bone in the femoral head and increases the anchoring force [16][17][18]. (b) e spiral blade can be locked by itself with strong holding force, which can play the role of antirotation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Both the TFNA and PFNA systems are provided by the same manufacturer with a similar design concept of providing better fixation stability in osteoporotic fractures by impacting the bone on the helical blade. The TFNA was developed to improve its precursor, the trochanteric fixation nail (TFN) system (Depuy Synthes, West Chester, PA, USA), by introducing a lateral relief cut to reduce impingement on the lateral cortex and a bump cut on the mid-portion of the proximal aperture to improve fatigue strength [2,[16][17][18]. Despite its proposed advantages, a recent study by Lambers et al reported 16 cases of TFNA implant breakage, raising concerns about its safety [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 3-dimensional (3D) plates of different sizes, thicknesses and holes were created in Space Claim to be used in analysis. The femur model was obtained from 3D computed tomography scans used in previous studies in the literature [16,17]. In the 3D femur model, a fracture was created by removing the segment in the transverse plan from the femur diaphysis area.…”
Section: Methodsmentioning
confidence: 99%